Changes in running economy following downhill running - Chen, T. C.; Nosaka, K.; Tu, J.-H. (Journal of Sports Sciences, 2007)
In this study, we examined the time course of changes in running economy following a 30-min downhill (-15%) run at 70% peak aerobic power (&Vdot;O2peak). Ten young men performed level running at 65, 75, and 85%&Vdot;O2peak (5 min for each intensity) before, immediately after, and 1 - 5 days after the downhill run, at which times oxygen consumption (&Vdot;O2), minute ventilation, the respiratory exchange ratio (RER), heart rate, ratings of perceived exertion (RPE), and blood lactate concentration were measured. Stride length, stride frequency, and range of motion of the ankle, knee, and hip joints during the level runs were analysed using high-speed (120-Hz) video images. Downhill running induced reductions (7 - 21%, P < 0.05) in maximal isometric strength of the knee extensors, three- to six-fold increases in plasma creatine kinase activity and myoglobin concentration, and muscle soreness for 4 days after the downhill run. Oxygen consumption increased (4 - 7%, P < 0.05) immediately to 3 days after downhill running. There were also increases (P < 0.05) in heart rate, minute ventilation, RER, RPE, blood lactate concentration, and stride frequency, as well as reductions in stride length and range of motion of the ankle and knee. The results suggest that changes in running form and compromised muscle function due to muscle damage contribute to the reduction in running economy for 3 days after downhill running.